2022
DOI: 10.3389/fsurg.2022.919886
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and validation of a prediction score for postoperative delirium in geriatric patients undergoing hip fracture surgery or hip arthroplasty

Abstract: IntroductionPostoperative delirium is a common complication of patients undergoing hip fracture surgery or arthroplasty and is related to decreased survival time and physical function. In this study, we aim to build and validate a prediction score of postoperative delirium in geriatric patients undergoing hip fracture surgery or hip arthroplasty.MethodsA retrospective cohort of geriatric patients undergoing hip fracture surgery or hip arthroplasty was established. Variables of included patients were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Clinicians should be vigilant for POD in patients who present with these features during the perioperative period. In recent years, a variety of risk prediction models have been developed to predict POD risk in geriatric patients with hip fractures ( Kim et al, 2020 ; Oberai et al, 2021 ; Shen et al, 2022 ; Table 2 ), which enable delirium risk stratification for hip fracture patients and facilitate the development of strategies for POD. Adapted from the AWOL (Age, WORLD backward, Orientation, illness severity) delirium prediction tool for medical inpatients Douglas et al (2013) , Whitlock et al (2020) developed a perioperative delirium risk stratification tool called AWOL-S (Age, WORLD backward, Orientation, illness severity, Surgery-specific risk) for elective surgical patients.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Clinicians should be vigilant for POD in patients who present with these features during the perioperative period. In recent years, a variety of risk prediction models have been developed to predict POD risk in geriatric patients with hip fractures ( Kim et al, 2020 ; Oberai et al, 2021 ; Shen et al, 2022 ; Table 2 ), which enable delirium risk stratification for hip fracture patients and facilitate the development of strategies for POD. Adapted from the AWOL (Age, WORLD backward, Orientation, illness severity) delirium prediction tool for medical inpatients Douglas et al (2013) , Whitlock et al (2020) developed a perioperative delirium risk stratification tool called AWOL-S (Age, WORLD backward, Orientation, illness severity, Surgery-specific risk) for elective surgical patients.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…The mean of the original CCI in this cohort was 5.1 (SD ± 2.0) and 4.6 (SD ± 1.9) for the adjusted CCI. A previous study of a hip fracture population reported a similar CCI value of 5 (SD ± 2) (Shen et al 2022 ). The observed 30-day and 1-year mortality rates in this study were 8.6% and 25.9%, respectively.…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, the random forest model also performed best in our previous study on POD prediction [ 10 ]. Shen J. et al developed a risk score for predicting POD in hip fracture patients, using nine variables, and achieving an AUC of 0.833 [ 25 ]. Yang Y. et al constructed a nomogram for POD prediction using only three variables and achieved an AUC of 0.84.…”
Section: Discussionmentioning
confidence: 99%